2022
DOI: 10.1002/ccd.30083
|View full text |Cite
|
Sign up to set email alerts
|

5‐Year outcomes after transcatheter aortic valve implantation: Focus on paravalvular leakage assessed by echocardiography and hemodynamic parameters

Abstract: Objectives We sought to assess the impact of echocardiographic and hemodynamic grading of paravalvular leakage (PVL) after transcatheter aortic valve implantation (TAVI) on the prediction of 5‐year mortality. PVL after TAVI is known to influence outcome after TAVI. Yet, present available data of long‐term outcomes and especially the comparison of different modalities for measurement of PVL is little. Methods We performed a retrospective single‐center cohort study and compared the prognostic value of echocardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
0
8
1
1
Order By: Relevance
“…In addition to conventional angiography and echocardiography, haemodynamic assessment, such as aortic regurgitation index (ARI) [ 22 ], may be considered in relation to VD-AR. However, in our TAVI cohort neither ARI nor ARI ratio was predictive of mortality [ 18 ] and the same was true for the current subset (data not shown).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…In addition to conventional angiography and echocardiography, haemodynamic assessment, such as aortic regurgitation index (ARI) [ 22 ], may be considered in relation to VD-AR. However, in our TAVI cohort neither ARI nor ARI ratio was predictive of mortality [ 18 ] and the same was true for the current subset (data not shown).…”
Section: Discussionmentioning
confidence: 75%
“…Based on the grading of aortic valve insufficiency according to Sellers et al [ 21 ], PVR is visually graded on angiography as “none/trace”, “mild”, “moderate” and “severe” [ 11 , 13 , 22 ]. Severe PVR requires immediate repair and there is ample evidence of increased mortality in patients left with moderate PVR after TAVI [ 5 , 6 , 9 , 12 , 13 , 18 ]. Yet, evidence on the prognostic impact of mild PVR is conflicting [ 6 , 9 , 12 , 13 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given this evidence, the incidence of significant PVL has been significantly reduced due to the development of prosthetic valve technology. However, recent reports have suggested that even mild PVL could be a determinant of worse midterm and long‐term outcomes following TAVI 80–82 . It is noteworthy that newer generation valves with a taller skirt could seal the bioprosthesis and reduce the severity of PVL 83 .…”
Section: Complications Associated With Heart Failure Hospitalization ...mentioning
confidence: 99%
“…However, recent reports have suggested that even mild PVL could be a determinant of worse midterm and long-term outcomes following TAVI. [80][81][82] It is noteworthy that newer generation valves with a taller skirt could seal the bioprosthesis and reduce the severity of PVL. 83 Moreover, a recent report by Akodad et al demonstrated that late dilatation (a median of 4.6 months) for symptomatic transcatheter heart valve dysfunction reduced the transvalvular gradient and the PVL to less than or equal to mild in all cases with greater than mild PVL without inducing any complications.…”
Section: Paravalvular Leakagementioning
confidence: 99%